The Narration of China (Part 1) : Ancient China between the Lines - Zhi, Chen (Ancient Languages and Civilizations, 2025)
Part One of the Festschrift honoring William H. Nienhauser invites readers to explore the fascinating world of ancient Chinese texts through a scholarly lens. The collected articles investigate how already in early times, formerly lost texts were recovered, studied, and edited in order to produce the literature now accessible to us. They analyze how ancient poems inscribed on newly unearthed bamboo slips can be dated according to their rhyme structure and linguistic nuances. And readers will further delve into the vivid accounts of kings and heroes recorded by Sima Qian in his Records of the Grand Historian and gain insights into his personal reflections on figures like Zhang Qian and the developing trade routes between East and West. In sum, this volume provides a comprehensive insight into the rich tapestry of pre-Qin and Han era literature and historiography.